A virtual 'hour on-call': creating a novel teaching programme for final-year undergraduates during the COVID-19 pandemic. (2021) - Harrison, Nicholas; Sharma, Shiv; Heppenstall-Harris, Gabriel; Sommereux, Lauren; Griffin, Michael; Evans, Catherine; Barnes, Alexandra
No abstract available